DROUGHT RESISTANCE VARIETIES AND LINES OF DURUM WHEAT (Eurasian Journal of Academic Research, 2026)
The article presents the results of research on the assessment of drought resistance of the studied varieties and lines of durum wheat under laboratory conditions in an experimental plot of competitive variety testing. To study drought resistance in laboratory conditions, such parameters of durum wheat varieties and lines as germination and coleoptile length in a sucrose solution were analyzed, and varieties and lines with high drought resistance were selected.